Human–environment dynamics during the Iron Age in the Lofoten Islands, Norway - Balascio, Nicholas L.; Wickler, Stephen (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2018)
This is an Accepted Manuscript of an article published by Taylor & Francis in Norsk Geografisk Tidsskrift on 1 May 2018, available online: http://www.tandfonline.com/10.1080/00291951.2018.1466831 . Integrated archaeological and paleoenvironmental investigations provide long-term perspectives on human–environment interactions. In the North Atlantic region, early human settlements were established in marginal agricultural environments and were susceptible to various environmental stressors. The Lofoten Islands have had an important role in the history of this region, particularly during the Iron Age, when Lofoten developed from pioneering agricultural settlements to a prominent node of power and trade under Viking chieftains. Iron Age developments in Lofoten were concurrent with significant natural environmental changes, including variations in climate and sea level. However, there has not been a comprehensive investigation of their influence on early settlements. The purpose of the study is to review Iron Age cultural developments in Lofoten using published archaeological data and paleoenvironmental records of past climate and sea-level change, and to present specific examples of the intersection of early human development and natural environmental changes. The findings show that climate changes probably influenced agricultural phases and that relative sea-level variations had important impacts on maritime developments. In conclusion, the findings demonstrate that human–environment interactions were significant factors in Lofoten’s history and the authors suggest specific areas for future research.